Kritik Historisisme Epigrafis dalam Pembacaan Wahyu: Studi atas Kisah Martir Najran dan Akhir Kerajaan Ḥimyar - Taryudi, Taryudi (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This article critically examines Norbert Nebes' reading of the tragedy of the Martyrs of Najran and the collapse of the Kingdom of Himyar, particularly in relation to the interpretation of QS al-Burūj [85]:4. Using a philological-historical and critical hermeneutic approach, this study shows that Nebes' epigraphic historicism—although excellent in reconstructing the geopolitics of early 6th-century South Arabia—tends to reduce the revelation of the Qur'an to a historical artifact that is equated with inscriptions and hagiographic texts. This reduction ignores the theological and rhetorical autonomy of the Qur'an as a discourse that interprets history, rather than merely reflecting it. Through a methodological dialogue with Angelika Neuwirth's discursive paradigm and Irfan Shahid's humanistic approach, this article asserts that the tragedy of Najran cannot be adequately understood through historical verification alone, but requires a reading that integrates the meaning of faith, human experience, and moral transformation. This study argues that an adequate methodology for religious studies must transcend historical positivism by balancing philological precision and theological reflection, so that revelation is understood as a meaningful event that continues to live across time.